Characterization and Electrochemical Properties of P(VdF‐co‐HFP) Based Electrospun Nanocomposite Fibrous Polymer Electrolyte Membrane for Lithium Battery Applications. Issue 11 (2nd September 2014) - Padmaraj, O.; Venkateswarlu, M.; Satyanarayana, N.; Aggarwal, Suresh K.
Abstract Effect of ZnAl2O4 nanofillers concentration on the physical and electrochemical properties of electrospun P(VdF‐co‐HFP) based nanocomposite electrolyte membranes were studied. By optimizing the spinning process parameters, the bead free and an average range (0.5–1.0 µm) of diametered fibrous membranes were developed using an electrospinning technique. The nanocomposite fibrous membrane with 5 wt% ZnAl2O4 fillers showed reduction of crystallinity, good thermal stability and smooth morphology were studied by X‐ray diffraction, differential scanning calorimetry and scanning electron microscopy techniques. The fibrous P(VdF‐co‐HFP) copolymer and nanocomposite P(VdF‐co‐HFP)/ZnAl2O4 polymer electrolytes were prepared by soaking the prepared electrospun fibrous membranes in 1 M LiPF6 in EC: DEC (1 : 1, v/v) and evaluated the wet‐ability properties by electrolyte uptake method. The activated nanocomposite fibrous polymer electrolyte membrane with 5 wt% ZnAl2O4 fillers content shows high ionic conductivity of 1.59×10−3 S cm−1 at room temperature and good electrochemical stability window higher than 4.3 V. Electrochemical performance of Li/PE, NCPE/LiCoO2 CR 2032 coin cells containing the prepared fibrous polymer electrolyte (PE) and nanocomposite polymer electrolyte (NCPE) membranes with 5 wt% ZnAl2O4 filler content is evaluated at current density 0.1 C‐rate over the potential range 2.8–4.2 V.